Aspergillus spp. and azole-resistance characterization on filtering respiratory protective devices from waste sorting industry - Viegas, Carla (2020)
Project EXPOsE. Project nº 23222 (02/SAICT/2016). Project Waste FRPD. Project IPL/2018/WasteFRPD_ESTeSL.